Development of a schistosomiasis vaccine. (3rd May 2016) - Molehin, Adebayo J.; Rojo, Juan U.; Siddiqui, Sabrina Z.; Gray, Sean A.; Carter, Darrick; Siddiqui, Afzal A.
ABSTRACT: Schistosomiasis is a neglected tropical disease (NTD) of public health importance. Despite decades of implementation of mass praziquantel therapy programs and other control measures, schistosomiasis has not been contained and continues to spread to new geographic areas. A schistosomiasis vaccine could play an important role as part of a multifaceted control approach. With regards to vaccine development, many biological bottlenecks still exist: the lack of reliable surrogates of protection in humans; immune interactions in co-infections with other diseases in endemic areas; the potential risk of IgE responses to antigens in endemic populations; and paucity of appropriate vaccine efficacy studies in nonhuman primate models. Research is also needed on the role of modern adjuvants targeting specific parts of the innate immune system to tailor a potent and protective immune response for lead schistosome vaccine candidates with the long-term aim to achieve curative worm reduction. This review summarizes the current status of schistosomiasis vaccine development.